Anisotropic, Hydrogel Microparticles as pH-Responsive Drug Carriers for Oral Administration of 5-FU - Serena P. Teora; Elada Panavaité; Mingchen Sun; Bas Kiffen; Daniela A. Wilson (MDPI AG, 2023)
In the last 20 years, the development of stimuli-responsive drug delivery systems (DDS) has received great attention. Hydrogel microparticles represent one of the candidates with the most potential. However, if the role of the cross-linking method, polymer composition, and concentration on their performance as DDS has been well-studied, still, a lot needs to be explained regarding the effect caused by the morphology. To investigate this, herein, we report the fabrication of PEGDA-ALMA-based microgels with spherical and asymmetric shapes for 5-fluorouracil (5-FU) on-demand loading and in vitro pH-triggered release. Due to anisotropic properties, the asymmetric particles showed an increased drug adsorption and higher pH responsiveness, which in turn led to a higher desorption efficacy at the target pH environment, making them an ideal candidate for oral administration of 5-FU in colorectal cancer. The cytotoxicity of empty spherical microgels was higher than the cytotoxicity of empty asymmetric microgels, suggesting that the gel network's mechanical proprieties of anisotropic particles were a better three-dimensional environment for the vital functions of cells. Upon treatment with drug-loaded microgels, the HeLa cells' viability was lower after incubation with asymmetric particles, confirming a minor release of 5-FU from spherical particles.